Kansas school district leaders' handbook for maximizing nontraditional donations and grant funding - Pekarek, Brian D. (Kansas State University, 2013)
The purpose of this study was to research, develop, and validate a handbook of effective strategies that Kansas school district leaders can use to increase their ability to maximize their school districts’ nontraditional funding. Kansas School District Leaders’ Handbook for Maximizing Nontraditional Donations and Grant Funding was developed using the research and development methodology as recommended by Gall, Borg, and Gall (2007) through a seven-step development cycle. The review of the literature, the needs assessment, and the proof of concept survey provided information for developing the outline and initial prototype for the final handbook. Non-educators in Kansas who had significant success in acquiring nontraditional funding and fostering entrepreneurial leadership throughout the state served as experts for the preliminary field test. Revisions were then made based on their feedback. The main field test was conducted with a representative group of Kansas superintendents, who were the potential users of the guide. These two groups of experts provided feedback by using a Likert scale and survey responses about the content and format of the handbook. Final revisions were based on the main field test evaluators’ feedback. The conclusions from the research project were: (1) there was a strong need for Kansas school district leaders to be educated regarding the proactive steps they can take in order to increase the possibilities for additional grant and donation funding for their school districts; (2) since Kansas’ state educational funding had been significantly reduced in Kansas during the years between 2008-2012, schools districts were forced to look at non-traditional options that could ease the strain on the districts’ general fund or provide additional resources for the schools during a downturn in the economy; (3) the development of a comprehensive handbook that blended theory, research, and practice for instructional leaders on how to conduct effective campaigns on acquiring additional revenue could be used to develop a mindset for Kansas school leaders to one that was focused more on the principles of entrepreneurial leadership.
Keywords: Nontraditional funding; School finance; Educational grants; Entrepreneurial leadership; Kansas superintendents; Educational Administration (0514); Educational evaluation (0443); Educational leadership (0449)